2012
DOI: 10.1088/0022-3727/45/36/365401
|View full text |Cite
|
Sign up to set email alerts
|

Single laser based dual-wavelength ablation technique for emission enhancement during LIBS

Abstract: In this paper, a novel method of the dual-wavelength (laser-induced breakdown spectroscopy LIBS) technique using a single laser system is proposed and demonstrated. Experiments are performed using a pulsed Nd3+ : YAG laser with a pair of 355–1064 nm and also with 532–1064 nm. The shorter wavelength laser is used for ablation and plasma formation, and the fundamental wavelength (1064 nm) is used for plasma re-excitation. The proposed dual-wavelength LIBS technique is used for lunar simulant samples under differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
12
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 19 publications
1
12
0
Order By: Relevance
“…used a combination of a fast PMT-high bandwidth oscilloscope to obtain the temporal evolution of a plasma obtained on simulant lunar soil. 21…”
Section: Introductionmentioning
confidence: 99%
“…used a combination of a fast PMT-high bandwidth oscilloscope to obtain the temporal evolution of a plasma obtained on simulant lunar soil. 21…”
Section: Introductionmentioning
confidence: 99%
“…It is worthwhile to compare Antony's work reported in Ref. [28] with this work. Although both works adopted 532+1064-nm wavelength combination based on single Nd:YAG laser, 1064-nm laser certainly contributed to sample ablation thus deteriorate the spatial resolution in Antony's work due to cross beam geometrical arrangement; however, in this work, 1064-nm laser did not ablate any samples during the reheating process, this ensured a high spatial resolution which was only determined by 532-nm laser due to orthogonal geometrical arrangement.…”
mentioning
confidence: 66%
“…In most of the DP-LIBS studies mentioned above, researchers paid less attention on spatial resolution improvement than on signal enhancement and two laser systems were usually required. Antony et al [28] reported a cross beam DP-LIBS for analysis of lunar simulant samples in which only single Nd:YAG laser was required. In their experiment, 532-nm laser from one Nd:YAG laser was used to ablate sample and 1064-nm laser from the same laser was used to reheating the plasma to get enhance plasma emission.…”
mentioning
confidence: 99%
“…The enhancement mainly arises from the metastable excited state of helium atom which is utilized to induce the delayed excitation of hydrogen atoms during ablation. On the other hand, the methods of preheating and reheating of plasma using dual lasers have been used to enhance the characteristic emissions at the expense of the background noise elevation (Babushok et al, 2006;Shoursheini et al, 2009Shoursheini et al, , 2010Killinger et al, 2007;Antony et al, 2012).…”
Section: Introductionmentioning
confidence: 99%